SUPPLY-CHAIN OF NATURAL RUBBER IN INDONESIA - Bustanul Arifin (Jurnal Manajemen & Agribisnis, 2005)
The study examines the supply chain of natural rubber production in Indonesia and assessing the transmission of prices to rubber growers and provides recommendations for a suitable scheme that would help to ensure high production standards and a sustainable return for natural rubber production.  The frameworks to examine the performance of supply chain of rubber marketing rely mostly on the efficiency level of marketing system of natural rubbers, including the value chain principles in marketing margin, and revealed price transmission from consumers to growers. The results show that the roles of subdistrict middlemen are extremely crucial in moving up the slabs from the village level to urban areas, where trader-brokers are expecting the slabs to be forwarded directly to crumb-rubber factories.  Changes in world price, hence the profits being accumulated by traders and rubber factories, are not transmitted properly to rubber farmers and/or sharetappers. Information asymmetry, the access over price information, and immediate response of rubber growers to the change in world price could explain this non-cointegration in price data between growers and exporters.  In the near future, the policy reforms in supply chain of natural rubber marketing in Indonesia should carefully address these issues in a more comprehensive manner.  Finally, in order to contribute to the positive environmental and social benefits, the major challenge for natural rubber production system in the future is how to integrate a high productivity promotion of new clonal rubber varieties and a decision for land use practices that satisfy sustainable resource management and ensure acceptable quality of environments in the forest margin.